COVID-19 in CKD Patients: Lessons from 553 CKD Patients with Biopsy-Proven Kidney Disease - Juan León Román; Clara García-Carro; Irene Agraz; Nestor Toapanta; Ander Vergara; Alejandra Gabaldón; Irina Torres; Roxana Bury; Cinthia Baldallo; Daniel Serón; María José Soler (Karger Publishers, 2021)
Introduction: Chronic kidney disease (CKD) patients infected with COVID-19 are at risk of serious complications such as hospitalization and death. The prognosis and lethality of COVID-19 infection in patients with established kidney disease has not been widely studied. Methods: Data included patients who underwent kidney biopsy at the Vall d'Hebron Hospital between January 2013 and February 2020 with COVID-19 diagnosis during the period from March 1 to May 15, 2020. Results: Thirty-nine (7%) patients were diagnosed with COVID-19 infection. Mean age was 63 ± 15 years and 48.7% were male. Hypertension was present in 79.5%, CKD without renal replacement therapy in 76.9%, and cardiovascular disease in 64.1%. Nasopharyngeal swab was performed in 26 patients; older (p = 0.01), hypertensive (p = 0.005), and immunosuppressed (p = 0.01) patients, those using RAS-blocking drugs (p = 0.04), and those with gastrointestinal symptoms (p = 0.02) were more likely to be tested for COVID-19. Twenty-two patients required hospitalization and 15.4% died. In bivariate analysis, mortality was associated with older age (p = 0.03), cardiovascular disease (p = 0.05), chronic obstructive pulmonary disease (p = 0.05), and low hemoglobin levels (p = 0.006). Adjusted Cox regression showed that low hemoglobin levels at admission had 1.81 greater risk of mortality. Conclusions: Patients with COVID-19 infection and kidney disease confirmed by kidney biopsy presented a mortality of 15.4%. Swab test for COVID-19 was more likely to be performed in older, hypertensive, and immunosuppressed patients, those using RAS-blocking drugs, and those with gastrointestinal symptoms. Low hemoglobin is a risk factor for mortality.